Raising aluminum foil fists: how to speak about anger in transplant medicine - Alexandra Vieux Frankel; Eva-Marie Stern (Frontiers in Sociology)
Dominant narratives of solid-organ transplantation foreground vocabularies of gratitude. Solid-organ transplantation is often celebrated in biomedicine for its high-tech innovation and specialization. But transplantation also includes the organizations that oversee the distribution of donated organs to potential recipients who disproportionately outnumber available organs. Wait-listing for transplant weighs urgency and fitness for transplant against availability, as individuals must simultaneously demonstrate that their conditions are severe enough to warrant transplantation while also showing they are well enough to withstand the transplant procedure that is meant to return the individual from critical illness to able-bodied health. This article considers how promises of cure make affective demands on transplant recipients. Dominant transplantation narratives and metaphors frame transplantation as “rebirth” and the “gift of life.” But this framework constrains transplant recipients' affective and emotional repertoires, positioning gratitude as the primary—if not only—acceptable feeling for performing that the “gift of life” was deserved. Such narrowly sanctioned possibilities for expression elide the affective complexities of transplant recipients' experiences and foreclose opportunities for expressing anger and frustration. This paper unpacks the politics of verbalizing anger among solid-organ transplant recipients at an urban North American hospital. Using arts-based sensory ethnographic interviews with 27 participants, this paper draws on affect theory to understand how transplant recipients critique and protest curative imaginaries while also upholding them. Theorizations from Critical Disability Studies provide generative ways to question negative feelings and more fully understand recipients' experiences.